DETERMINING THE VALUE OF CONIFEROUS WOOD DRYING USED IN DRY, HOT CLIMATE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article shows indicators of wood shrinkage coefficients, drying stages, the effect of wood shrinkage density.